1997
DOI: 10.1002/(sici)1097-4644(1997)27+<7::aid-jcb4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of cancer chemopreventive agents in China

Abstract: Since the late 1970s, a comprehensive search for cancer chemopreventive agents has been established in our Institute. A series of new retinoids have been synthesized and screened on the basis of established methodologies of experimental chemoprevention in vitro as well as in vivo. Pharmacological studies demonstrated that N-4-(carboxyphenyl)retinamide (RII) induces cell differentiation of HL-60 cells and inhibits dimethylnitrosamine-induced carcinogenesis of the forestomach in mice, 7,12-dimethylbenz[a]anthrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The 18α-isomer of Glycyrrhetinic Acid was more potent in these effects than the 18βisomer. Rui (1997) found that Glycyrrhetinic Acid inhibited ear edema induced by croton oil in mice. No other details of this study were given.…”
Section: Other Antiviral Activitiesmentioning
confidence: 99%
“…The 18α-isomer of Glycyrrhetinic Acid was more potent in these effects than the 18βisomer. Rui (1997) found that Glycyrrhetinic Acid inhibited ear edema induced by croton oil in mice. No other details of this study were given.…”
Section: Other Antiviral Activitiesmentioning
confidence: 99%